Design of a nondestructive two-in-one instrument for measuring the polarization and energy spectrum at an X-ray FEL facility. (6th October 2017) - Zhang, Qingmin; Deng, Bangjie; Chen, Yuanmiaoliang; Liu, Bochao; Chen, Shaofei; Fan, Jinquan; Feng, Lie; Deng, Haixiao; Liu, Bo; Wang, Dong
Abstract: The free electron laser (FEL), as a next-generation light source, is an attractive tool in scientific frontier research because of its advantages of full coherence, ultra-short pulse duration, and controllable polarization. Owing to the demand of real-time bunch diagnosis during FEL experiments, precise nondestructive measurements of the polarization and X-ray energy spectrum using one instrument are preferred. In this paper, such an instrument based on the electron time-of-flight technique is proposed. By considering the complexity and nonlinearity, a numerical model in the framework of Geant4 has been developed for optimization. Taking the Shanghai Soft X-ray FEL user facility as an example, its measurement performances' dependence on the critical parameters was studied systematically, and, finally, an optimal design was obtained, achieving resolutions of0.5% 0.5% for the polarization degree and0.3 0.3 eV for the X-ray energy spectrum.